KUNCI KINERJA OPTIMAL: HARMONISASI BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN SISTEM INFORMASI - Mennita, Ria; Sarasmitha, Citra; Rahmawati, Anas; Dharma, Intan Novia Indira (Ekonomi dan Bisnis: Berkala Publikasi Gagasan Konseptual, Hasil Penelitian, Kajian, dan Terapan Teori, 2023)
The increasing of business competition after the pandemic has encouraged the business world to be more dynamic and able to develop adaptive and effective Management Accounting Information System (MAIS) management strategies. This study aims to determine the importance of alignment between work environment, work culture and organizational culture on business performance through the effectiveness of the company's management accounting information system in electronic stores in Malang city. Data collection was carried out using a questionnaire. The data analysis tool used Structural Equation Modeling (SEM) analysis with AMOS 23. The sample consisted of 159 respondents who were employees and supervisors of electronic stores in Malang City. The results showed that the work environment and organizational culture have a significant positive influence on SIAM and organizational performance. In this case, work culture does not have a significant influence on organizational performance. The significance of this study shows that the influence of environment and culture on organizational performance can be achieved through the effectiveness of information systems in stores, so that employees can make maximum good contributions to the organization.